Catalytic Acid−Base Groups in Yeast Pyruvate Decarboxylase. 3. A Steady-State Kinetic Model Consistent with the Behavior of both Wild-Type and Variant Enzymes at All Relevant pH Values - Sergienko, Eduard A; Jordan, Frank (Biochemistry (Easton), 2001)
The widely quoted kinetic model for the mechanism of yeast pyruvate decarboxylase (YPDC, EC 4.1.1.1), an enzyme subject to substrate activation, is based on data for the wild-type enzyme under optimal experimental conditions. The major feature of the model is the obligatory binding of substrate in the regulatory site prior to substrate binding at the catalytic site. The activated monomer would complete the cycle by irreversible decarboxylation of the substrate and product (acetaldehyde) release. Our recent kinetic studies of YPDC variants substituted at positions D28 and E477 at the active center necessitate some modification of the mechanism. It was found that enzyme without substrate activation apparently is still catalytically competent. Further, substrate-dependent inhibition of D28-substituted variants leads to an enzyme form with nonzero activity at full saturation, requiring a second major branch point in the mechanism. Kinetic data for the E477Q variant suggest that three consecutive substrate binding steps may be needed to release product acetaldehyde, unlikely if YPDC monomer is the minimal catalytic unit with only two binding sites for substrate. A model to account for all kinetic observations involves a functional dimer operating through alternation of active sites. In the context of this mechanism, roles are suggested for the active center acid−base groups D28, E477, H114, and H115. The results underline once more the enormous importance that both aromatic rings of the thiamin diphosphate, rather than only the thiazolium ring, have in catalysis, a fact little appreciated prior to the availability of the 3-dimensional structure of these enzymes.